A PRELIMINARY ANALYSIS OF Eucalyptus STAND DENSITY FROM A HIGH-DENSITY UAV LASER SCANNING DATA - Philipe Sebastião Guerra, Saulo; Silberger, Romain; Seube, Nicolas; Berger, Louise; de Jesus Eufrade-Junior , Humberto (9° Congresso Florestal Brasileiro, 2022)
Remote sensing using Light Detection and Ranging technology has been increasingly used to quantify forest resources. Thus, the objective of this study was to test algorithms for counting the number of trees in UAV-LS data. The study was performed in a six-year-old stand of Eucalyptus sp. The census of the experimental area werecarried out. The point cloud was obtained using the sensor coupled to a drone. The algorithms li2012 and dalponte2016 were used to segment the trees. In order to preliminary evaluate the algorithms for the quantification of individual trees, the number of predicted individuals in the area was compared with the number observed in the field. The algorithms presented relative accuracy in the count number.